Perbandingan Kekuatan Hukum Alat Bukti Otentik dan Perjanjian Bawah Tangan (Studi Kasus Perkara Nomor: 939/Pdt.G/2018/PN Dps) - Ronaldo Darmawan; Anak Agung Sagung Laksmi Dewi; Ni Made Sukariyati Karma (Jurnal Interpretasi Hukum, 2021)
Every citizen in Indonesia must obey the prevailing regulations for the creation of public order and security. The law itself functions as a unifying nation and binds everyone with sanctions. If there are citizens who violate the rules, they will be subject to sanctions according to the applicable rules. This study aims to determine the comparison of the legal strength of authentic deed evidence with underhand deeds and to analyze the judges' considerations in their decision on the legal strength of underhand deeds over authentic deeds. The method in this research is a type of normative legal research which is carried out by the method of recording and studying based on legal materials. The data source used comes from documents. The results showed that the proving power of underhand deeds was not as strong as authentic deeds because underhand deeds did not have three types of strength such as authentic deeds, namely external, formal, and material proof. But it is only limited to formal and material strength with a much lower weight than the authentic deed.